1996
DOI: 10.1021/jf950358s
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Aflatoxin in Pistachios. 3. Distribution in Pistachio Process Streams

Abstract: The distribution of aflatoxin concentration has been measured by sampling 19 process streams ranging from 1 to 1000 nuts/sample. The 19 streams comprise substantially the entire sorted product of one producer for crop year 1992. Similar results were obtained by another producer for 1993. The fraction of total aflatoxin accounted for by each process stream was computed. It was concluded that 90% of aflatoxin is contained in 4.6% of (low-quality) product; removal of this product would reduce average aflatoxin fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 9 publications
0
29
1
Order By: Relevance
“…Mycological analyses revealed that the most frequently isolated fungi from nuts were Aspergillus strains 14. In particular, peanuts and pistachio nuts are highly susceptible to damage by the toxigenic A. flavus and A. parasiticus , which can produce the deleterious toxin aflatoxin 11, 15–17. Gürses13 examined 18 peanuts samples, bought from a Turkish market, and found that seven of them were positive for the presence of aflatoxin B 1 with an average concentration of 43 ng g −1 peanut.…”
Section: Introductionmentioning
confidence: 99%
“…Mycological analyses revealed that the most frequently isolated fungi from nuts were Aspergillus strains 14. In particular, peanuts and pistachio nuts are highly susceptible to damage by the toxigenic A. flavus and A. parasiticus , which can produce the deleterious toxin aflatoxin 11, 15–17. Gürses13 examined 18 peanuts samples, bought from a Turkish market, and found that seven of them were positive for the presence of aflatoxin B 1 with an average concentration of 43 ng g −1 peanut.…”
Section: Introductionmentioning
confidence: 99%
“…With AFB 1 levels on the rise, it is increasingly important to study it's movement during processing and to adjust processing methods to minimize the impact of contaminated almonds. The distribution of AFB 1 in tree nuts and postharvest sampling theory have been reported (Schade, McGreevy, King, Mackey, & Fuller, 1975;Schatzki, 1995Schatzki, , 1996Schatzki & Ong, 2000, 2001Schatzki & Pan, 1996;Whitaker, Giesbrecht, Wu, Hagler, & Dowell, 1994). Most of the AFB 1 is found in a small number of heavily contaminated nuts (Schade et al 1975;Schatzki, 1996;Schatzki & Ong, 2000).…”
Section: Practical Applicationsmentioning
confidence: 94%
“…Step 12: Sorting (by Hand or Electronic Eye) (Schatzki and Pan, 1996) Levels of aflatoxin will be significantly reduced at this step due to the removal of shellstained, discolored and defective pistachios, which contain high levels of aflatoxin. Step 13: Packaging…”
Section: Step 3: Fresh Pistachio Receivingmentioning
confidence: 99%